Vinegar Volatile Organic Compounds: Analytical Methods, Constituents, and Formation Processes - Xie, Zhenzhen; Koysomboon, Chanisara; Zhang, Huan; Lu, Zhenming; Zhang, Xiuyan; Chen, Fusheng (Frontiers in Microbiology, 2022)
Vinegar is an acid condiment shared by all over the world. According to the raw materials, vinegars can be mainly divided into fruit and cereal ones, both of which possess unique aroma and flavor characteristics and the corresponding volatile organic compounds (VOCs). Many studies around vinegar VOCs’ (VVOCs) sorts, analytical methods and forming mechanisms have been done. In this review, the main categories of vinegars and their distribution in the world are briefly introduced, then VVOCs’ analytical and identified methods, types and forming processes are summarized. And the VVOCs’ research directions are discussed and prospected as well. According to the literatures as we can search, it is the first time to systematically review the analytical methods, sorts and formation mechanisms of VVOCs, which will make the readers better understand the vinegars’ aromas and flavors and their production mechanisms.